Distributed parameter modeling of fluid transmission lines. (October 2021) - Elkhashap, Ahmed; Rüschen, Daniel; Abel, Dirk
Abstract: Fluid transmission lines represent a main element in a wide spectrum of systems and applications such as water supply and circulation networks found in both domestic as well as in industrial facilities. Modeling of fluid transmission lines is therefor a highly important task for analysis, monitoring and control purposes. In this contribution, first principles model representing the propagation and interaction of the fluid's temperature is presented. Using this general mathematical representation, two simulation models are realized based on different simplifying assumptions, i.e. pure convective flow, effective convective diffusive flow. The two simulation models are then used to describe an exemplary circulation network present at the head quarters of the company VIEGA. The experimental setup as well as two measured data sets used for parameter identification and validation of the two model instances are presented. Finally both model instances are compared against the experimental data outlining the advantages and disadvantages of each model. For the case of non zero flow both models showed high accuracy in the prediction of the water temperature distribution with mean percentage error (MPE) below 4%. For the cases with time periods of zero flow, the first model failed to maintain the high prediction accuracy, where the prediction's MPE showed significantly higher values up to 10%. However, the second model showed robustness regarding flow stagnation preserving the high prediction accuracy with MPE below 3% and maximum absolute error below 5 [ ° C ] . The computational burden of the models is analyzed for the simulations performed. The models feasibility for real-time applications can be claimed as the models showed an average step computation time below 20 [ms] for a highly optimized C-code implementation on a development computer. Highlights: Models of fluid transmission lines for real-time monitoring and control Distributed parameter model formulation, i.e. spatial resolution preservation Method of Characteristics solution for efficient prediction of fluid thermal behavior First principle approximate PDE model considering thermal diffusion Accurate temperature prediction even for zero flow case Model identification and validation for a real-world water circulation network